The Perception of Using Learning Management System In Higher Education: An Empirical Investigation Using TAM - Diyenti Rusdin; Marzuki Marzuki; Ismail Yunus H; Nila Irmayani; Agung Rinaldy Malik (Interference: Journal of Language, Literature, and Linguistics, 2022)
Abstrak. The goal of this study is to identify the lecturers perceptions of using a learning management system (LMS) in the teaching of E-Learning procedures in English Department of Madako University. It was a qualitative study that involved three Lecturers and four students as participants. These persons served as English Department lecturers during the academic years 2020/2021. The TAM theoretical framework is applied to explain the uptake of LMS in terms of its perceived ease of use and utility. It was revealed that as long as the professor use LMS are (a) in perceiving ease of use, it is seen that the score of lecturers is 4,7 percent strongly agreed and agreed 52,3 percent while the score of uncertain lecturers is 42,80 percent (b) The sense of usefulness is strongly agreed upon by 17 percent of respondents, and agreed upon by 56 percent of respondents, despite the fact that 27 percent are suspicious. As for the usage of LMs, 22 percent strongly agree, 44 percent agree, and 33 percent doubt (c) this is the attitude toward which they should be utilized. (d) behavioral intention to use, where the mean score of the lecturer is agreed upon at 67 percent and doubted at 66,65 percent; and (e) job relevance, where the mean score of the lecturer is agreed upon at 67 percent and doubted at 49,95 percent. The researcher comes to the conclusion that the perception of English instructors regarding the employment of LMS is a neat idea.Keywords: LMS, Lecturer Perception, E-Learning